2022
DOI: 10.1021/acs.chemmater.2c00289
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the S=12 Kagome Ferromagnet within a Family of Metal–Organic Frameworks

Abstract: Kagome networks of ferromagnetically or antiferromagnetically coupled S 1 2 1 2= ferromagnetic kagome layers that are coupled antiferromagnetically via their extended organic pillaring linkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…More recently, MOF glasses, a disordered form of MOFs, are finding niche applications. This virtual collection catalogues recent MOF advances featured in Chemistry of Materials from 2022 to 2023, with an accompanying editorial by Laura Gagliardi and Omar Yaghi that outlines three critical future directions for MOFs …”
Section: Opening Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, MOF glasses, a disordered form of MOFs, are finding niche applications. This virtual collection catalogues recent MOF advances featured in Chemistry of Materials from 2022 to 2023, with an accompanying editorial by Laura Gagliardi and Omar Yaghi that outlines three critical future directions for MOFs …”
Section: Opening Remarksmentioning
confidence: 99%
“…Magnetic Kagome lattices are tremendously interesting but rare in MOFs. Clark and co-workers describe a family of copper carbonate based pillared-layered ferromagnetic–antiferromagnetic Kagome networks which could represent important models for pursuing novel quantum and topological states of matter …”
Section: Structural Design Transformation and Engineeringmentioning
confidence: 99%
“…4,5 In general, MOFs can exhibit a whole range of magnetic properties including 3D Hoffman complexes in diamagnetic or paramagnetic states, 6 standard ferromagnetism, 7 itinerant ferromagnetism, 8 or antiferromagnetism. 9 The last one has been recently reported to occur on S = 1/2 Kagome networks with Cu 2+ coordination ions with 2D layers of magnetic moments sandwiched between organic linkers. Moreover, many of them manifest a spin-switching effect also known as spin crossover (SCO), which is a transition between the lowspin (LS) state and the high-spin (HS) state induced by various stimuli such as light, temperature, pressure, and chemical reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In general, MOFs can exhibit a whole range of magnetic properties including 3D Hoffman complexes in diamagnetic or paramagnetic states, standard ferromagnetism, itinerant ferromagnetism, or antiferromagnetism . The last one has been recently reported to occur on S = 1/2 Kagome networks with Cu 2+ coordination ions with 2D layers of magnetic moments sandwiched between organic linkers.…”
Section: Introductionmentioning
confidence: 99%
“…We note that the zinc-substituted synthetic barlowite, Zn x Cu 4– x (OH) 6 FBr, is another leading material with characteristic QSL properties . Also, some copper-based metal organic frameworks (MOFs) with kagome lattices have been synthesized. , The flexibility and complexity of the organic linkers in these MOFs require comprehensive structural studies in order to fully describe the observed magnetic properties.…”
Section: Introductionmentioning
confidence: 99%